Website-Based Management of Guidance and Counseling Laboratory Administration at the University of Technology - Ari Prasetyoaji; Awalia Novita Lestari (Universitas PGRI Yogyakarta, 2026)
The research was motivated by the limited use of technology in administrative media, especially in the administration of counseling laboratories. Technology-based universities should apply technology properly. The purpose of this research: 1) To find out the conventional administration media switches based on the website. 2) To determine the validity of website-based counseling laboratory administration media products. The research used the R&D (Research and Development) method of the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Purposive sampling was used, with the subjects involved 10% of the total counseling students. Data collection in the study used observation and questionnaire methods. The results of the validity of media experts 75%, material experts 78%, member users 92% and non-member users 88%. The benefits of this research: 1) Digital media provides convenience to visitors to the counseling lab. 2) As a basic material for further researchers. This study has several limitations, including the inability of iOS users to use the camera and the lack of exit attendance for non-member visitors. For researchers, this development can determine the percentage of interest in visiting the counseling lab. Keywords: counseling laboratory administration, technology utilization, website development